The role of social media in our life and study - Muxtarova, Ilmira Azamat kizi (Science and Education, 2023)
In recent days, in our digital world, almost all people has one or several social networking accounts. There are several of social networking sites like Telegram, Facebook, Twitter, Google, Snapchat and Instagram. As well as, these kinds of social networking sites hava had a great impact on our life and education. And they have advantages and disadventages. With the help of social networks we can be aware of all the news in the world, find any kind of information, study online and communicate with people around the world. Without doubt, using the social networks more than norm may lead to Internet addiction or some kind of illnesses. Using them normally is benefical for our health, time consuming and and others.